Actuality Without Existence: The Jewish Figure in Heidegger's Notebooks. Issue 4 (1st October 2020) - Petropoulos, Georgios
ABSTRACT: This paper examines Heidegger's remarks about the worldlessness of Judaism in his Black Notebooks. In the first part of the paper I examine Heidegger's concept of the world in Being and Time and subsequent writings. In the second part, I analyze a distinction that Heidegger draws between mere human actuality and genuine human existence in a 1932 lecture course on The Beginning of Western Philosophy. This distinction, I suggest, relates to the development of Heidegger's thoughts on nihilism and what he conceives as its gravest danger. In the third part, I argue that the above-mentioned distinction can help us to better understand Heidegger's remarks on Judaism. In particular, I suggest that the Jewish figure comes to symbolize for Heidegger a kind of unessential human actuality that is irredeemably detached from the question of Being.